WRITING ANXIETY FACTORS IN FOURTH-SEMESTER ENGLISH STUDENTS AT MUHAMMADIYAH KOTABUMI UNIVERSITY - Rulik Setiani; Suprapto, Irawan; Waliya, Waliya (Language and Education Journal, 2024)
This research aimed to investigate the factors of students' anxiety in writing class and identify the dominant factors of students' anxiety in writing class. This research used descriptive qualitative research methods. The data from this research were taken from the interview results with 10 students in the fourth semester of the English education study program at Muhammadiyah Kotabumi University academic year 2021/2022. The instrument used in this research is an interview. In the data analysis technique, the data using the Miles and Huberman model which consists of reduction data, display data, and conclusion drawing/verification. The research findings reveal eight key factors contributing to students' anxiety in writing classes. These include inadequate writing practice (4 respondents), low self-confidence in writing (6 respondents), anxiety from writing (8 respondents), inadequate writing technique (8 respondents), pressure for perfect work (8 respondents), time pressure (9 respondents), problem with topic choice (9 respondents) and language difficulties (10 respondents). The three most prominent factors are language difficulties, time pressure, and topic choice issues, affecting 10 and 9 respondents. These findings provided important insights for educators to understand the sources of students' anxiety and develop effective strategies to help them overcome barriers in learning to write